Is PDQ-39 a reliable measure of quality of life of patients at advanced stages of Parkinson's disease considered for Deep Brain Stimulation - Maria Damianova; Desislava Gancheva; Kaloyan Gabrovski; Petar Karazapryanov; Yoana Milenova; Ivo D. Popivanov; Krasimir Minkin (Heliyon, 2024)
Purpose: Parkinson's disease (PD) significantly impedes, especially at its advanced stages, the health-related quality of life (QoL) of patients. The Parkinson's disease questionnaire (PDQ-39) is a widely-used measure assessing the impact of the disease on the patients' QoL. To date, the reliability of PDQ-39 has not been selectively evaluated for patients at a particular delineated stage of the PD progression. Against this backdrop, the study aimed firstly to evaluate comprehensively the internal consistency reliability of PDQ-39 and the constituent scales specifically for patients at the advanced stages of PD who were candidates for Deep Brain Stimulation (DBS) surgery, and secondly, to compare the Cronbach's alpha coefficients with those reported in other studies conducted with patients across all stages of the PD progression. Methods: The sample included 36 Bulgarian patients (29 men and 7 women) at advanced stages of PD (Hoehn and Yahr stage 4), PD duration, M = 11.06, SD = 3.50). The internal consistency reliability of the questionnaire and the constituent scales was assessed using three criteria: Cronbach's alpha coefficients, inter-item and item-total correlations. Results: The internal consistency reliability indicators were satisfactory for the entire instrument and for most of the scales and similar to those reported in previous studies. None of the scales had low internal consistency reliability results across the three criteria. Except for the Communication scale, seven of the eight scales had Cronbach's alpha values that were satisfactory or marginally below the cut off score. All scales had acceptable inter-item correlations. Three of the scales (Emotional Well-Being, Cognition and Communication) contained more than one item with non-satisfactory item-total correlations. With minor exceptions, the removal of the items with low item-total correlations either did not improve or improved marginally or even decreased the Cronbach's alpha coefficients of the respective scale. The Communication scale was the only scale with a Cronbach's alpha coefficient that was both low and comparatively different to other studies and had as well low item-total correlations for all constituent items, thus showing non-satisfactory results on two of the three internal consistency reliability estimates. In contrast, the Mobility scale met all three internal consistency reliability criteria. Conclusion: PDQ-39 is a reliable tool for assessing the QoL of patients at advanced stages of PD across multiple health-related domains. The questionnaire can be recommended for inclusion in the best practice guidelines for evaluating DBS candidacy and the efficacy of DBS treatment for patients’ QoL.